Consumo alcoólico e trauma em mulheres de países desenvolvidos e em desenvolvimento: estudo multicêntrico em prontos-socorros - Silva, Rosiane Lopes Da [UNIFESP] (2018)
Objectives: (1) to compare alcohol consumption by women treated in emergency rooms of developed and developing countries; (2) to delineate the sociodemographic profile of women who were assisted in emergency rooms with alcohol-related injuries; (3) to describe the occurrence of violent injury in women who consumed alcohol six hours before the injury. Methods: This is a prospective, cross-sectional study that evaluated women’s alcohol consumption treated in emergency rooms with complaints of non-fatal injuries within 6 hours. A questionnaire standardized by WHO was used; the self-report of alcohol consumption in the 24 hours prior to the contact and the blood alcohol concentration. A sample comprised of data collected from hospitals in 15 countries with 3937 women as part of two multicentre studies: ERCAAP (Emergency Room Collaborative Alcohol Analysis Project) and WHO (World Health Organization Collaborative Study on Alcohol Injuries ), both with the same research methodology. Descriptive analyses were performed with a 95% confidence interval (CI). Results: The average age of the women investigated was 39.85 years (SD = 18.23) and the minimum and maximum age ranged from 18 to 98 years. Women from developed countries with higher education (43.1% with high school education and 37.2% with college education) compared to women in developing countries (44.8% with elementary school education and 36.6% with high school education). More than half of the women in developing countries (52.3%) reported they had not drunk in the prior 12 months (abstinence) and 2.0% said they had been drinking on a daily basis. Overall, women in developing countries showed a higher frequency of binge drinking (consumption of 5 to 11 doses at a time) (33%) than women in developed countries (27.5%). Violence was more prevalent in developed countries (32.1%) than in developing countries (25.5%). Violent injuries were more prevalent in developing countries (18.1%) than in developed countries (8.6%). An association between violent injuries and frequency of consumption in the last 12 months was observed, both in developing countries (p = 0.0069) and in developed countries (p = 0.0082). It was also discovered that the percentage of violent injuries in abstinent women (20.3%), who rarely consumed (14.4%), occasionally (14.2%) and frequently (27.5%) from developing countries was higher than in women from developed countries (7.1%, 6.2%, 8.7% and 12.4%, respectively). Conclusions: Although injuried women from developing countries had the highest prevalence of abstinence rates and the lowest rates of daily alcohol consumption, they drank more dangerously and had more violent injuries than those from developed countries. The data of this study indicates that the occurrence of injuries among women and the association with alcohol consumption should consider socioeconomic differences, patterns of consumption and situations of violence in order to influence the implementation of prevention, health promotion and treatment for this population.